The Influence Of Work Motivation And Work Environment Conditions On Employee Performance : Empirical And Theoretical Study - Shafira Maharani Firdaus; Wawan Prahiawan; Liza Mumtazah Damarwulan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to analyze the influence of work motivation and work environment on the performance of employees in an organization. Work motivation and work environment are important factors that can affect staff performance levels. In the context of human resources management, it is important for organizations to take these factors into account in order to improve productivity and achieving the goals of the organization as a whole. Through an empirical and theoretical study approach, the study highlights the importance of creating a conducive working environment and increasing employee motivation in an effort to optimal performance. The results of this research are expected to provide useful insights for managers and organizational leaders in managing human resources more effectively.